Optimal phosphotungstinate concentration for polypyrrole linear actuation and energy storage. Issue 1 (5th November 2018) - Zondaka, Zane; Harjo, Madis; Khan, Md Asaduzzaman; Khanh, Tran Thien; Tamm, Tarmo; Kiefer, Rudolf
Abstract: Phosphotungstic acid (PTA) and the phosphotungstinates have been shown to be beneficial additives for polypyrrole (PPy) electropolymerization. The goal of this work was to study the PTA concentration effect on the electrodeposition of PPy doped with dodecylbenzenesulfonate (DBS), in view of electronic, linear actuation and sensory properties. Cyclic voltammetry, square wave potential steps and square wave amperometry conducted with isometric and isotonic electro-chemo-mechanical deformation measurements were performed in aqueous lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) electrolyte. The films deposited from 0.01 M PTA showed the highest strain—as much as 20%. The highest conductivities, however, were obtained with films deposited from 0.005 M PTA—in range of 44 S cm −1, accompanied by a high specific capacitance of 223 F g −1 . The highest PTA concentration (0.1 M) resulted in qualitatively different film properties and behavior.